2013
DOI: 10.9775/kvfd.2012.6989
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Effect of Resveratrol in Experimentally Induced Non-Sterile Clean Wound Inflammation in Rats

Abstract: The effects of resveratrol on haematological and biochemical parameters were investigated in rats that had inflammation induced by experimental non-sterile clean wound technique. Twenty four male Wistar-Albino rats weighing 250-300 g were placed into three groups of eight after matching for age, sex and weight. In the sham-operated and resveratrol-treated groups, a 4-cm incision was made on the median line of the rats in order to create a wound. Resveratrol group was administrated resveratrol daily at a dose o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Considering the anti-inflammatory characteristic of resveratrol [ 41 ], the observed decrease in WBC was expected. Hişmioğulları et al [ 42 ] also reported that WBC count was decreased in rats given resveratrol. One of the most important findings of this study was that some fluoride-induced hematological changes were improved in the group that received resveratrol with fluoride.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the anti-inflammatory characteristic of resveratrol [ 41 ], the observed decrease in WBC was expected. Hişmioğulları et al [ 42 ] also reported that WBC count was decreased in rats given resveratrol. One of the most important findings of this study was that some fluoride-induced hematological changes were improved in the group that received resveratrol with fluoride.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work on suppressive effects of resveratrol on leucocyte count has also been reported in rats [68]. This may be due to the anti-inflammatory property of resveratrol.…”
Section: Studies Of Resveratrol In Animals 21 Laboratory Animalsmentioning
confidence: 78%
“…From another aspect, trauma and wound healing could lead to significant elevation in pro-and anti-inflammatory cytokines [16,17] . Especially IL-1β and TNF-α, IL-6 and C-reactive protein, which is a predictor for acute-phase response and IL-10 have been used in biomarkers for monitoring traumatic inflammation and recovery period in clinically both human and veterinary medicine [18][19][20] .…”
Section: Kandir Keski̇nmentioning
confidence: 99%